2020
DOI: 10.1038/s41598-020-60734-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of peribrachial fat as a key determinant of brachial artery dilatation for successful arteriovenous fistula maturation in hemodialysis patients

Abstract: The functional quality of the inflow artery is one of the most important determinants of arteriovenous fistula (AVF) success. We evaluated the association of early optimal brachial arterial dilatation with a successful AVF maturation and assessed the role of peribrachial adipose tissue in determining brachial arterial distensibility. All patients underwent a preoperative vascular mapping with Doppler ultrasound (US), and only patients who had suitable vessels for AVF creation were enrolled (n = 162). Peribrach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The mean brachial artery diameter in mature patients was higher than in immature patients but also not significant (4.18±0.67 vs. 3.90±0.61, p=0.082). 10 In our study, the threshold values for predicting AVF maturation were preoperative brachial artery diameter of 3.85 mm (sensitivity 78.7% and specificity 60%) and cephalic vein diameter of 2.45 mm (83% sensitivity and 72% specificity). In a study conducted by Ferring et al on 36 patients, the threshold value of the brachial artery was 3 mm, and the cephalic vein was 3 mm.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The mean brachial artery diameter in mature patients was higher than in immature patients but also not significant (4.18±0.67 vs. 3.90±0.61, p=0.082). 10 In our study, the threshold values for predicting AVF maturation were preoperative brachial artery diameter of 3.85 mm (sensitivity 78.7% and specificity 60%) and cephalic vein diameter of 2.45 mm (83% sensitivity and 72% specificity). In a study conducted by Ferring et al on 36 patients, the threshold value of the brachial artery was 3 mm, and the cephalic vein was 3 mm.…”
Section: Discussionmentioning
confidence: 65%
“…In Lee et al study, the AVF maturation failure rate was 13.59% out of 103 patients with DM. 10 Vernaglione et al found that AVF maturation failure was relatively high in women. This was thought to be caused by women generally having narrow blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The diameter of the brachial artery has an important role for the functionality of AVF, and there are few studies in the literature that support this theory. 23 In addition, Kakkos et al presented that the diameter of brachial artery ≤4.1 mm (lowest quartile) was an independent predictor of AVF functionality (57% vs 83% for larger arteries, P = .017). 24 Our study is one of the few that showed significant association between preoperative diameter of the brachial artery and functionality of AVF.…”
Section: Discussionmentioning
confidence: 99%
“…There was also a significant positive correlation between the diameter of the brachial artery and achieved BF of AVF at the fourth week after creation. The diameter of the brachial artery has an important role for the functionality of AVF, and there are few studies in the literature that support this theory 23 …”
Section: Discussionmentioning
confidence: 99%